The impact of tournament horizon scheme and relative performance information on performance - Kusufi, Muhammad Syam; Rohma, Frida Fanani; Muhammad, Erfan (Universitas Swadaya Gunung Jati, 2020)
AbstractThe quality of human resources is one of primary keys to the success of company. Indicators of high-quality human resources can be reflected in improvements in employee performance. Stream of research has examined various efforts to encourage employee performance improvement, one of which is through the optimization of incentive schemes. This study investigates the effect of the tournament scheme horizon and the publication frequency of relative performance information on performance. This study uses an experimental method with a 3 x 2 factorial design between subjects. The horizontal scheme is manipulated into 3 (Hybrid vs. Repeated vs. Grand), while the frequency of publication of relative performance information is manipulated to 2 (high vs. low). The results of this study indicate that the tournament scheme horizon as a basis for monetary incentives is quite effective in driving performance improvement. In contrast, the publication frequency of relative performance information as an effort to compare social conditions and not as a basis for monetary incentives is not strong enough to trigger performance improvements. As a rational economic man, the attempt to pursue incentives can prove to be a trigger for efforts to drive performance improvements that are greater than the pursuit of non-monetary incentives.Keywords: Employee performance; Monetary; Non-monetary; Publication frequency of relative performance information; Tournament.AbstrakKualitas sumber daya manusia merupakan salah satu kunci utama suksesnya perusahaan. Indikator dari tingginya kualitas sumber daya manusia dapat tercermin dari peningkatan kinerja karyawan. Perkembangan penelitian telah mengkaji beragam upaya untuk mendorong peningkatan kinerja karyawan salah satunya melalui optimalisasi skema insentif. Penelitian ini menginvestigasi pengaruh horizon skema turnamen dan frekuensi publikasi informasi kinerja relatif terhadap kinerja. Penelitian ini menggunakan metode eksperimen dengan desain faktorial 3 x 2 antar-subjek. Horizon skema turmanen dimanipulasi menjadi 3 (Hibrida vs. Berganda vs. Tunggal) sementara frekuensi publikasi informasi kinerja relatif dimanipulasi menjadi 2 (tinggi vs. rendah). Hasil penelitian ini menunjukkan bahwa horizon skema turnamen sebagai dasar insentif moneter cukup efektif mendorong peningkatkan kinerja. Sementara frekuensi publikasi informasi kinerja relatif sebagai upaya perbadingan kondisi secara sosial dan tidak sebagai dasar pemberian insentif moneter, tidak cukup kuat memicu peningkatan kinerja. Sebagai manusia ekonomi yang rasional upaya untuk mengejar insentif terbukti dapat menjadi pemicu usaha untuk mendorong peningkatan kinerja yang lebih besar daripada upaya pengejaran insentif non-moneter.Kata kunci: Informasi kinerja relative; Kinerja karyawan; Moneter; Non-moneter; Turnamen